UUM Web-Based To Project Time Tracking System (PTTS) - Alfartas, Khaled Omran (2008)
The development of the Internet, networking and data processing technologies tighter with increasing complexity of the data and electronics design process has provided many needs and opportunities for wide area collaboration in complex system design and because development teams are not necessary centralized support of distribute teams is needed. This research has presented the development of an integrated Web-based Project Time Tracking System hoped to improving the coordination and speed up of work by supervisors and coordinators on UUM students' project. The paper also discussed the requirement model of the system as well as the development of the prototype tool incorporated as module in the web-based system for Project Time Tracking System. Finally, a usability test was conducted to approve the efficiency and applicability of the new developed web-based system. It was found that the results were satisfactory and such system is highly required by Universiti Utara Malaysia.